Pinealectomy increases and exogenous melatonin decreases leptin production in rat anterior pituitary cells: an immunohistochemical study - Kus, I; Sarsilmaz, M; Colakoglu, N; Kukner, A; Ozen, OA; Yilmaz, B; Kelestimur, H (Acad Sciences Czech Republic, Inst Physiology, 2004)
Melatonin, the main hormone of the pineal gland, informs the body about the environmental light and darkness regimen, which in turn contributes to the photoperiodic adaptation of several physiological functions. Leptin, the hormone secreted mainly by adipocytes and some other tissues including the pituitary, informs the brain about the mass of adipose tissue, which plays an important role in energy homeostasis. Melatonin has been shown to decrease circulating leptin levels. It is currently not known whether melatonin has an effect on leptin synthesis in the pituitary. The aim of this study was to immunohistochemically examine the effects of pinealectomy and administration of melatonin on leptin production in the rat anterior pituitary. The pituitary samples obtained from 18 male Wistar rats including sham-pinealectomized, pinealectomized and melatonin-injected pinealectomized groups were immunohistochemically evaluated. Immunostaining of leptin was moderate (3+) in sham-pinealectomized rats, heavy (5+) in pinealectomized rats and low (1+) in melatonin-treated pinealectomized rats, respectively. The present results indicate that pinealectomy induces leptin secretion in anterior pituitary cells, and this increase of leptin synthesis can be prevented by administration of melatonin. Thus, melatonin seems to have both physiological and pharmacological effects on leptin production in the anterior pituitary of male rats.
Keywords: leptin; melatonin; pinealectomy; anterior pituitary; rat